DIALOG TRANSFORMATIF AGAMA DAN KEKERASAN - Andri Fransiskus Gultom (Bahasa Indonesia, 2018)
Nowadays, the rise of violence in religion has created new issues on humanity. The pluralism of religion has been indicated as a trigger of conflicts and unfinished debates. Many conflicts develop in many places because each group claims that their religions have an absolute truth whereas the other religion do not. In brief, this exclusive attitude and paradigm has made each group of religion tends to exclude other religions, therefore all efforts to create peace and harmony among religzous people are difficult to be implemented. In other word being exclusive in religion makes disharmony. This fact is not regarded as "taboo", because people have been accustomed to "take for granted" the truth in their religions. Asking the truth becomes the difficulty and challenge to create peace. The question is, how to create the dialogues among all religions in the world, especially in Indonesia? The hope to create peace, and love in among religions zn Indonesia still needs the dialog in practice.